Sulfasalazine Sensitizes Polyhematoporphyrin-Mediated Photodynamic Therapy in Cholangiocarcinoma by Targeting xCT - Zheng, Yan-Wen; Miao, Xiong-Ying; Xiong, Li; Chen, Bo; Kong, Fan-Hua; Zhou, Jiang-Jiao; Liu, Zhong-Tao; Wen, Yu; Zhang, Zi-Jian; Zou, Heng (Frontiers in Pharmacology, 2021)
Cholangiocarcinoma (CCA), which is highly malignant, shows a relatively poor prognosis, due to the insensitivity of the tumour to chemotherapy and radiotherapy. Photodynamic therapy (PDT) has become a promising palliative therapeutic option for patients with unresectable cholangiocarcinoma (CCA), while the functional amount of ROS is limited by intracellular redox systemen. Sulfasalazine (SASP), a well-known anti-inflammatory agent, which also acts as an inhibitor of the amino acid transport system xc (xCT), decreases the intracellular glutathione (GSH) level, thus weakening the antioxidant defence of the cell by inhibition of the antiporter. However, the combination of SASP and PDT remains unexplored. We have reported that polyhematoporphyrin (PHP)-mediated PDT inhibits the cell viability of CCA cells and organoids. Furthermore, in PHP-enriched HCCC-9810 and TFK-1CCA cells, SASP enhances the sensitivity to PHP-mediated PDT through a GSH-dependent mechanism. We found that PHP-PDT can up-regulate xCT expression to promote cells against overloaded ROS, while SASP reduces GSH levels. After the combination of SASP and PHP-PDT, cell viability and GSH levels were significantly inhibited. xCT was also observed to be inhibited by SASP in human organoid samples. Our findings suggest that, in combination with PDT, SASP has potential as a promising approach against CCA.